Late metachronous isolated pancreatic metastasis from renal cell carcinoma mimicking a pancreatic neuroendocrine tumor - Hyung Ku Chon; Keum Ha Choi (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Chon HK, Choi KH. Late metachronous isolated pancreatic metastasis from renal cell carcinoma mimicking a pancreatic neuroendocrine tumor. Turk J Gastroenterol 2019; 30(5): 489-91.